Visible Learning: Feedback - John Hattie, Shirley Clarke (2018)
eedback is arguably the most critical and powerful aspect of teaching and learning. Yet, there remains a paradox: why is feedback so powerful and why is it so variable? It is this paradox which Visible Learning: Feedback aims to unravel and resolve.